2015
DOI: 10.3390/en9010013
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Hydrogen, Lignin and Sodium Hydroxide from Pulping Black Liquor by Electrolysis

Abstract: Black liquor is generated in Kraft pulping of wood or non-wood raw material in pulp mills, and regarded as a renewable resource. The objective of this paper was to develop an effective means to remove the water pollutants by recovery of both lignin and sodium hydroxide from black liquor, based on electrolysis. The treatment of a 1000 mL of black liquor (122 g/L solid contents) consumed 345.6 kJ of electric energy, and led to the generation of 30.7 g of sodium hydroxide, 0.82 g of hydrogen gas and 52.1 g of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Figure 7 compares FT-IR spectra of the lignin and calcium lignin. The curves of the calcium lignin material exhibit the characteristic absorption peaks of lignin at 3,427, 2,929, and 1,597 cm −1 corresponding to -OH, -CH, and phonic ring groups, respectively [23][24][25]. The peaks at 1,415 cm −1 were the characteristic adsorption peaks of O-Ca groups [26,27].…”
Section: Ft-ir Analysis Resultsmentioning
confidence: 98%
“…Figure 7 compares FT-IR spectra of the lignin and calcium lignin. The curves of the calcium lignin material exhibit the characteristic absorption peaks of lignin at 3,427, 2,929, and 1,597 cm −1 corresponding to -OH, -CH, and phonic ring groups, respectively [23][24][25]. The peaks at 1,415 cm −1 were the characteristic adsorption peaks of O-Ca groups [26,27].…”
Section: Ft-ir Analysis Resultsmentioning
confidence: 98%
“…[85] Nong et al also demonstrated that electrolysiso fB Lu sing ac ationic electrolytic reactor equipped with ac ation-exchange membrane can result in the recovery of 80.4 %N aOH and 76 %b iomass residue while cogenerating 0.82 go fhydrogen gas. [158] More recently,H ibino et al [159] and Caravaca et al [160] both studied hydrogen production assisted by lignin electrolysis in a polymer electrolyte membrane reactor at PtFe/C and Pt-Ru anodes, respectively.Inthe study by Hibino et al an onset voltage of 0.25 Vand temperature of 100-200 8Cr esulted in 100 % current efficiency for hydrogen production.T emperature was found to enhance I-V curve (current vs. cell-voltage curve) characteristics due to ad ecrease in ohmic and polarization resistances. Further improvement of the current density was achieved at 150 8Cv ia the use of at hinner electrolyte membrane and the addition of H 3 PO 4 -impregnated lignin.…”
Section: Electrochemical Degradation Of Lignin For Hydrogen Co-producmentioning
confidence: 99%
“…Nong et al. also demonstrated that electrolysis of BL using a cationic electrolytic reactor equipped with a cation‐exchange membrane can result in the recovery of 80.4 % NaOH and 76 % biomass residue while cogenerating 0.82 g of hydrogen gas …”
Section: Electrocatalytic Treatment Of Ligninmentioning
confidence: 99%
“…The determined water content shows that the solid content of the sample is 18 wt.%. That value is in the classic hardwood BL's solid content range [8,10,30,39,60]. Regarding the elemental analysis, it should be referred that comparison with literature data is difficult, as the composition of BL changes according to the type of wood, tree, and the process adopted by the mill.…”
Section: Characterization Of the Spent Liquor Samplesmentioning
confidence: 99%